On-farm participatory varietal selection - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
An on-farm participatory varietal selection (PVS) of stress-tolerant varieties (both submergence and salinity) was held in Bac Lieu Province, South Vietnam to test adaptability in the locality and acceptability by the farmers. An approach used to evaluate was preference analysis, where farmers were allowed to set criteria and select the varieties they most want to grow.